2021
DOI: 10.1371/journal.ppat.1009480
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive organ penetration and high vector transmissibility of epidemic dengue virus-2 Cosmopolitan genotype in a transmission mouse model

Abstract: Dengue virus (DENV) causes dengue fever and severe hemorrhagic fever in humans and is primarily transmitted by Aedes aegypti and A. albopictus mosquitoes. The incidence of DENV infection has been gradually increasing in recent years due to global urbanization and international travel. Understanding the virulence determinants in host and vector transmissibility of emerging epidemic DENV will be critical to combat potential outbreaks. The DENV serotype 2 (DENV-2), which caused a widespread utbreak in Taiwan in 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 47 publications
1
16
0
Order By: Relevance
“…As for the needlestick experiment, naïve male and female mice bitten by infected mosquitoes could become infected (40% infectivity rate) as evidenced by detectable DENV serum titers (Figure 3B). Successful transmission of DENV was associated with a loss of body weight 12, 22 , as seen in mice that were either infected through MT or through direct tail vein inoculation (Figure 3C). Infected mice also died (Figure 3D), confirming the existence of MT as a lethal method of transmission for DENV.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…As for the needlestick experiment, naïve male and female mice bitten by infected mosquitoes could become infected (40% infectivity rate) as evidenced by detectable DENV serum titers (Figure 3B). Successful transmission of DENV was associated with a loss of body weight 12, 22 , as seen in mice that were either infected through MT or through direct tail vein inoculation (Figure 3C). Infected mice also died (Figure 3D), confirming the existence of MT as a lethal method of transmission for DENV.…”
Section: Resultsmentioning
confidence: 90%
“…The clinical isolate 2015 DENV-2 (TW2015) 12 was propagated in Aedes aegypti and Vero cells, and the viral titer was determined via plaque-formation assay using BHK- 21 C15 cells. Vero cells were grown at 37°C, 5% CO2 in 1× Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 5% fetal bovine serum (FBS), 1× MEM nonessential amino acid solution, and 1× antibiotic-antimycotic solution.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of virulence of dengue virus, two amino acids, E50A and G67A, located within the first transmembrane domain (TMD1) of the NS4A protein was shown to attenuate virus replication, decrease NS4A oligomerization and reduce stability ( Lee et al, 2015 ). Additionally, Lin et al had previously used the Taiwan DENV-22015 outbreak strain and successfully established a full transmission cycle using this virus ( Lin et al, 2021 ). They demonstrated that the pre-membrane and envelope genes were key virulence determinants in the host and had high transmissibility of the Taiwan 2015 strain in mosquitoes.…”
Section: Discussionmentioning
confidence: 99%